PERLINDUNGAN HUKUM PADA HUBUNGAN KERJA PENAHANAN IJAZAH SEBAGAI OBJEK JAMINAN ANTARA PERUSAHAAN DAN PEKERJA - Panotogomo, Agung Wibowo Purnomo; Poernomo, Sugeng Hadi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study focuses on legal protection in the employment relationship of diploma detention as an object of guarantee between the company and the worker. workers are potentials who are already bound by a working relationship with the entrepreneur by receiving wages or other forms of remuneration. A company is a person who has a place for an activity to produce services or goods in any form, it can also be referred to as an institution or organization that manages together for profit or profit. The purpose of this research is to protect workers whose diplomas are held by the company based on Law No. RI. 13 of 2003 concerning Manpower. To find out and analyze how the legal protection for workers whose diplomas are withheld by the company and To find out and analyze how the legal protection for workers is if the company continues to withhold diplomas after a dispute resolution decision is made. This research method is a type of normative law. This research itself has used the statutory approach method and then also used the conceptual approach method. The results of this study indicate that the protection or rules for workers whose diplomas are held by the company. provide a benefit to the community, as well as become input for the government or the authorities in their field